Assistive robots to improve the independent living of older persons: results from a needs study. (2nd January 2021) - Fiorini, Laura; De Mul, Marleen; Fabbricotti, Isabelle; Limosani, Raffaele; Vitanza, Alessandra; D'Onofrio, Grazia; Tsui, Michael; Sancarlo, Daniele; Giuliani, Francesco; Greco, Antonio; Guiot, Denis; Senges, Eloïse; et al.
Abstract: Background: More than 70% of elderly people age 80 and older are experiencing problems in personal mobility. Assistive robotics can represent a concrete support providing also a support for caregivers, clinicians and nurses by reducing their burden. Methods: A total of 20 older people and 34 caregivers (formal and informal) were interviewed in Italy and the Netherlands to investigate and prioritize their needs concerning the personal mobility domains and their attitudes towards assistive robots. The data were analysed from a user point of view by means of thematic content analysis by underlying recurrent topics. Results: The results revealed four categories of needs from the perspective of the older individuals: instrumental needs, rehabilitation needs, personal safety and indoor activities of daily life. Additionally, the results underline how personal mobility issues influence different aspects of daily life. Complementarily, three categories of caregiver needs were also distinguished: instrumental needs, rehabilitation monitoring needs and checkup needs. The highest percentage of participants showed a positive expectation towards assistive robotics. Conclusions: The results were clustered according to the robot abilities (i.e., motion, interaction, manipulation, decision support and perception abilities) as a list of functional and technical requirements that should be developed to address all the needs related to the personal mobility. Robotic developer teams that work in this context could take advantage of this research. Additionally, this work can be used as a basis for clinicians and nurses working in geriatric units to understand how the robots can support and enhance their work. Implications for rehabilitation: The incidence of personal mobility limitations affects 35% of adults age 70 and older and 72% of people over 80 years of age. Assistive robots can support elderly people during daily tasks: they could promote their personal mobility acting as a supporting tool. The results of the needs analysis revealed four categories of needs from the perspective of the older individuals: instrumental needs, rehabilitation needs, personal safety, and indoor activities of daily life. Three categories of caregiver needs were also distinguished: instrumental needs, rehabilitation monitoring needs, and check-up needs.